Stabilizing effects of Ag doping on structure and thermal stability of FeN thin films. (28th December 2021) - Niti; Kumar, Yogesh; Seema; Reddy, V R; Vas, Joseph Vimal; Gupta, Surbhi; Stahn, Jochen; Gupta, Ajay; Gupta, Mukul
Abstract: In this work, we investigated the effect of Ag doping (2–20 at.%) on the phase formation of iron mononitride (FeN) thin films. Together with deposition of FeN using reactive dc magnetron sputtering, Ag was also co-sputtered at various doping levels between 2–20 at.%. We found that doping of Ag around 5 at.% is optimum to not only improve the thermal stability of FeN but also to reduce intrinsic defects that are invariably present in (even in epitaxial) FeN. Conversion electron Mössbauer spectroscopy and N K-edge x-ray near edge absorption measurements clearly reveal a reduction of defects in Ag doped FeN samples. Moreover, Fe self-diffusion measurements carried out using secondary ion mass spectroscopy depth-profiling and polarized neutron reflectivity in 57 Fe enriched samples exhibit an appreciable reduction in Fe self-diffusion in Ag doped FeN samples. Ag being immiscible with Fe and non-reactive with N, occupies grain-boundary positions as nanoparticles and prohibits the fast Fe self-diffusion in FeN.